Molecular DNA identification of blood sources fed on, for Culicine mosquitoes (Diptera: Culicidae) collected in the Songkhla province, southern Thailand - Theerakamol Pengsakul; Napadol Sudsom; Gregory Foakes; Kartik Bhatt; Marisa Eisenberg; Padet Siriyasatien (Songklanakarin Journal of Science and Technology (SJST), 2017)
Culicine mosquitoes are medically important vectors. Therefore, mosquito control measures are a crucial strategy to interrupt disease transmission. Collection of data on mosquito feeding patterns is crucial for developing an effective vector control strategy. The objective of this study was to use molecular biology methods to identify the sources of DNA in mosquito blood meals. The DNA from blood meals in the mosquito stomachs was extracted and amplified with multiplex PCR, using specific primer sets based on the mitochondrial cytochrome b gene, to identify the DNA sources among human, pig, goat, dog, cow, and chicken. Among the 297 mosquito samples collected in the Songkhla province of Thailand, in Aedes spp. mosquitoes the percentages positive for human, dog, pig, chicken, cow, a mixture of 2 vertebrate DNAs, or of 3, and negative (no identified DNA) were 61.90, 2.38, 2.38, 0.60, 0.60, 4.18, 1.20 and 26.79% respectively. In Culex spp. blood meals the rank order was different: fractions positive for chicken, human, dog, cow, goat, pig, a mixture of 2 or 3 vertebrate DNAs, and negative were 40.83, 10.00, 5.00, 4.17, 1.67, 0.83, 8.32, 3.32 and 25.83% respectively. This study shows that feeding behaviors of the two species differ, with most Aedes spp. blood meals containing human blood, while Culex spp. had primarily consumed chicken blood. An improved understanding of the feeding behaviors of mosquitoes could contribute to new, more effective strategies for the control of mosquito populations.